2010
DOI: 10.1182/blood.v116.21.2296.2296
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbidity In Event-Free Survival, Toxicity and Adherence to Treatment In Chronic Myeloid Leukemia Patients Treated with Imatinib

Abstract: 2296 Background: Comorbidity in cancer has been shown to be a major determinant in treatment selection and survival. The most used instrument for measuring comorbidity in Hematology is the Charlson comorbidities index (CCI). It is a list of 19 conditions with weight assigned from 1 to 6, derived from relative risk estimates of a proportional hazard regression model using clinical data. The ACE-27 is a 27 item comorbidity index for patients with cancer and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similarly, in the German CML‐Study IV, a higher CCI score was associated with lower OS probabilities in multivariable analysis, even after removal of age‐related components from the score 92 . A retrospective study in Brazil found significantly poorer EFS with imatinib and a higher rate of temporary treatment interruption secondary to toxicities and nonadherence in patients with higher CCI scores 93 . CCI stratification applied on a large cohort of older patients with CML (> 75 years) receiving imatinib treatment reported a significant correlation between CCI and survival (EFS and OS) 94 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, in the German CML‐Study IV, a higher CCI score was associated with lower OS probabilities in multivariable analysis, even after removal of age‐related components from the score 92 . A retrospective study in Brazil found significantly poorer EFS with imatinib and a higher rate of temporary treatment interruption secondary to toxicities and nonadherence in patients with higher CCI scores 93 . CCI stratification applied on a large cohort of older patients with CML (> 75 years) receiving imatinib treatment reported a significant correlation between CCI and survival (EFS and OS) 94 .…”
Section: Discussionmentioning
confidence: 88%
“… 92 A retrospective study in Brazil found significantly poorer EFS with imatinib and a higher rate of temporary treatment interruption secondary to toxicities and nonadherence in patients with higher CCI scores. 93 CCI stratification applied on a large cohort of older patients with CML (> 75 years) receiving imatinib treatment reported a significant correlation between CCI and survival (EFS and OS). 94 We hypothesize that the increased risk of recurrent imatinib‐related grade ≥ 3 ADRs observed in patients with higher CCI scores and pre‐existing pulmonary disease resulted in poor adherence or more frequent imatinib dose reductions/interruptions, leading to inferior molecular response rates and EFS.…”
Section: Discussionmentioning
confidence: 98%